Why has social democracy not developed in Turkey? Analysis of an atypical case - EMRE, YUNUS (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2015)
This paper scrutinizes why the Western European type of social democracy has not developed in Turkey. Both the historical backdrop and current constraints on the development of social democracy are examined. This paper argues that social democracy's failure in Turkey has stemmed from two reasons. On the one hand, historical and structural constraints that obstructed social democracy should be taken into account. On the other, social democratic movements suffered from an agency question. The leadership of the political parties, which defined themselves as centre-left entities, had a number of chances to build a genuine social democracy', but they chose alternative policy paths based on identity politics. This phenomenon too prevented the development of social democracy. The CHP (Cumhuriyet Halk Partisi, Republican People's Party) is the focal point of the paper since it has always been the main subject in the debates over social democracy in Turkey.
Keywords: Republican peoples party